Proposal for a Knowledge Management Framework applied to the development of software for Public Administration (Research, Society and Development, 2025)
Knowledge management (KM) is a subject that has been widely researched in academia and in public and private organizations. Over time, this topic has been strategically implemented as a management method to disseminate business information. Whether internally, by training personnel, or externally, by creating marketing and sales campaigns. Managing knowledge strategically in an organization that promotes improvements in the systems of other organizations, more than increasing productivity and business viability, consolidates its image and brand in the market, in addition to favoring its strategy and strengthening its culture. The objective of this article is to propose a knowledge management framework applied to software development for public administration. In the first stage of this research, a literature review was carried out to systematize the state of the art on the subject. In a second stage, the main areas of concentration of knowledge in the software development process were identified. References for the production and dissemination of this knowledge were also sought in the literature. Finally, the proposed knowledge management model was validated, contributing to software development organizations for public management in optimizing resources and decision-making by the manager for this area.